The Role of Human Resource Management in Enhancing the Capacity of Student Organizations at STIE Kalpataru: Manajemen Sumber Daya Manusia Dalam Mendorong Kapasitas Organisasi Kemahasiswaan di STIE Kalpataru - Rahman, Ali; Adi, Roni (UNIB Press, 2025)
This study aims to analyze the role of Human Resource Management (HRM) in enhancing the organizational capacity of student organizations at STIE Kalpataru. Student organizations require effective human resource management to grow and adapt within the dynamic environment of higher education. This research employs a qualitative approach using a case study method, involving student organization leaders and student affairs supervisors as informants. Data were collected through in-depth interviews, observation, and documentation. The findings indicate that HRM practices such as competency-based recruitment, continuous training, and structured performance evaluation have a positive impact on the organization's ability in program planning, activity management, and internal collaboration. Furthermore, leadership development and coaching significantly contribute to the sustainability of student organizations. These findings affirm that strategic human resource management is a key factor in strengthening the institutional capacity of student organizations. This study recommends the enhancement of HRM policies within student organizations to improve competitiveness and student professionalism in the future